Improved Injection Technique of Ethanol for Morton's Neuroma. (May 2020) - Pabinger, Christof; Malaj, Isabella; Lothaller, Harald; Samaila, Elena; Magnan, Bruno
Background: Morton's neuroma is a common cause of forefoot pain. Various conservative methods (injections of various pharmacologic agents) have been published with an outcome of 6%-75% success rate (free of pain in daily life) per injection. The aim of the present study was to assess the outcome of an improved localization technique, a higher dosage, and a higher percentage of ethanol. Methods: Using fluoroscopic and electroneurographic guidance, 2.5 mL of 70% ethanol were injected into 33 feet with a magnetic resonance imaging (MRI)–verified neuroma. We evaluated patients at up to 5-year follow-up. Results: A "success rate" of more than 82% per single injection (defined as free of pain in daily life) was achieved and no recurrence was seen over 5 years. All scores (visual analog scale; Short Form–36 subscales, American Orthopaedic Foot & Ankle Society ankle-hindfoot score) showed significant improvement ( P < .0001). Mean 1.2 injections were necessary. No significant side effects were seen. However, some mild pain persisted in some patients who participated in sports. Conclusion: The injection of 2.5 mL of 70% ethanol under fluoroscopic and electroneurographic guidance was a safe method for the treatment of MRI-verified Morton's neuromas. Combining the effect of a higher percentage of alcohol and a higher dosage and an improved localization technique resulted in a high rate of patients without pain. Level of Evidence: Level IV, cases series, prospective.